The transformation of the ktisis repository into a current research information system (CRIS) - Kounoudes, Alexia Dini; Zervas, Marios (My University, 2017)
Institutional repositories have played a major role in universities worldwide during the last decade. Such systems are developed with the aim to collect and disseminate the research activities of universities. They provide access to and showcase research outputs, and therefore they have become an essential infrastructure for universities. A repository provides the means to properly preserve research outputs and can also be used for research monitoring and assessment. In this case study, we concentrate on the transformation of Ktisis, the institutional repository of the Cyprus University of Technology, into a Current Research Information System (CRIS). A CRIS system records, processes, and presents metrics and figures related with research activity throughout its life cycle. Particular emphasis is given to the results of research activities (publications, patents, research data) and their connection with the environment within which they were created (researchers, organizations, funded programs and projects, research infrastructures, services). In this case study we will describe the procedures followed in order to transform Ktisis into a CRIS system together with the implementation of the integration of ORCID identifiers within the system. Particular attention will be paid to the challenges we came across throughout the process and how we overcame these difficulties and problems. Ktisis is the institutional repository developed and maintained by the Library and Information Services at the Cyprus University of Technology. Ktisis was created in 2008 using the open source software DSpace after the University’s Interim Governing Board made the decision that all the research products of academic members must be deposited in the Library. In subsequent years, the mandatory deposit of undergraduate, MSc and PhD theses was also imposed. In early 2015 it was decided that the Cyprus University of Technology (CUT) must become a member of ORCID and the Library undertook the project to integrate ORCID in its systems. At the same time the Library decided that the best way to move forward was to transform Ktisis into a CRIS system using DSpace-CRIS, an extension to DSpace, in order to integrate ORCID with the repository and to take advantage of all the functionalities provided by a CRIS system.
Keywords: Repositories; ORCID; CRIS